Position of Creditors After the Verdict of Bankruptcy Statement According to Law Number 37 of 2004 concerning Bankruptcy and PKPU: Kedudukan Kreditur Pasca Putusan Pernyataan Pailit menurut Undang Undang Nomor 37 Tahun 2004 tentang Kepailitan dan PKPU - Suhaila Zlkifli; Sunarto, Atika; Adnan, Muhammad Ali (Al-Mahkamah: Jurnal Hukum, Politik dan Pemerintahan, 2024)
The term "bankruptcy" is basically a matter, where the condition of the debtor (the debtor) who stops paying or does not pay his debts to the creditor (the party who gives the debt). Stopping paying does not mean not paying at all, but for some reason the payment of the debt is not working properly, so if the debtor files for bankruptcy, the debtor cannot pay his debts or has no more income for his company to make debt payments. This paper will discuss the position of creditors against debtors related to bankruptcy. The author finds that what regulates the position of creditors in bankruptcy is not only the UUKPKPU (Bankruptcy Law & Suspension of Debt Payment Obligations), but also the Civil Code (Burgerlijk Wetboek). This arrangement has several problems, namely the lack of clarity and incoherence in the laws and regulations. As a result, in practice the position of creditors becomes very weak. Creditors are divided into three, namely, concurrent creditors, separatist creditors, and preferred creditors. In relation to legal culture, law enforcers have recognized that the position of creditors in bankruptcy depends on the judge's decision and if the judge's decision is not in favor of creditors, this makes people prefer to resolve disputes through ways other than bankruptcy. Therefore the UUKPKPU (Bankruptcy Law & Suspension of Debt Payment Obligations) needs to clearly regulate the position of creditors.